2012
DOI: 10.1186/1471-2431-12-119
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index, sagittal abdominal diameter and waist-hip ratio with cardiometabolic risk factors and adipocytokines in Arab children and adolescents

Abstract: BackgroundSagittal abdominal diameter (SAD) is a novel anthropometric measure hypothesized to be a surrogate measure of visceral abdominal obesity in adults. This study aims to determine whether SAD is superior to other anthropometric measures such as body mass index (BMI) and waist to hip ratio (WHR) in terms of association to cardiometabolic risk and circulating adipocytokine concentrations in a cohort of Saudi children and adolescents.MethodsA total of 948 (495 boys and 453 girls) apparently healthy childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
3
9
0
1
Order By: Relevance
“…Our results are in line with studies in adults that have shown that the SAD was inversely associated with the clamp‐derived measure of insulin sensitivity . Studies have examined the relation between SAD and IR assessed by HOMA‐IR in pediatric population . However, these previous studies did not consider pubertal development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are in line with studies in adults that have shown that the SAD was inversely associated with the clamp‐derived measure of insulin sensitivity . Studies have examined the relation between SAD and IR assessed by HOMA‐IR in pediatric population . However, these previous studies did not consider pubertal development.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the differences in the statistical analyses between the studies, our results agree with that found in a study of Indian obese and overweight adolescents (aged 10‐18 years), that also showed that the SAD was positively correlated with the HOMA‐IR after adjusting for age and sex . However, contrary to our data, a study of Saudi adolescents (aged between 10 and 17 years), did not observe significant correlation between the SAD and the HOMA‐IR after adjusting for sex and age . However, their statistical analysis was conducted with SAD z ‐scores.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Findings of previous studies comparing the ability of BMI and measures of abdominal adiposity to identify cardiometabolic risk factors are conflicting. WC has been found to be associated with cardiometabolic risk factors independent of BMI in some studies [14, 15] while others have found that measures of abdominal adiposity are not better than BMI for the identification of cardiometabolic risk [16, 17]. A recent study reported measures of abdominal adiposity were not better predictors of VAT than BMI in children [18], which may explain these negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…Diğer taraftan 22±2 yaşındaki öğrencilerin incelendiği bir çalışmada kardiyovasküler risk faktörlerinden hipertansiyon için VKİ'nin, anormal serum lipidleri için bel çevresi ve bel/boy oranının iyi bir prediktör olduğu gösterilmiştir (23). VKİ'nin diğer parametrelere daha üstün olduğunu bildiren çalışmalar da vardır (24). Bizim çalışmamızda, kardiyovasküler risk faktörlerini öngörmede bel/boy oranının VKİ, VYY ve bel/kalça oranına göre daha iyi bir prediktör olduğu görüldü.…”
Section: Discussionunclassified